The antitumor promoting activity of 2-himachalen-7-ol in two-stage mouse skin carcinogenesis test - Daher, CF (2016)
Cedrus libani ssp. libani (Pinaceae) is a plant used in traditional medicine for the treatment of various diseases. 2-Himachalene-7-ol, previously isolated from the plant, possesses in vitro anticancer activity [1]. The present study investigates the chemopreventive effects of 2-himachalene-7-ol on 7,12-dimethyl benz(a)anthracene (DMBA)/12-O-tetradecanoyl phorobol-13-acetate (TPA) skin tumorigenesis model in mice. The stem xylem was extracted with hexane and the obtained oil was subjected to silica gel chromatography to isolate 2-himachalen-7-ol. Papilloma were initiated on shaved dorsal skin using DMBA and promoted twice weekly using TPA for 20 weeks [2]. Animal groups were treated once weekly with 2-himachalen-7-ol via different routes: gavage (50 mg/kg), intraperitoneally (IP 10, 25, or 50 mg/kg) or topically (0.2mL of 0.5, 1 or 2.5%). Tumor yield, and volume were compared with those of non-treated control and cisplatinum-treated groups (IP 2.5 mg/kg). Liver and kidney toxicity as well as body weight changes were also investigated. Data were analysed using ANOVA. At week 16 all animal groups treated with either 2-himachalen-7-ol or cisplatinum had relatively less papilloma number (0 – 52%) and volume (30 – 66%; p < 0.05). At week 20 the number of papilloma was highest in the cisplatinum and lowest in the 2-himachalen-7-ol IP 10 mg/kg groups. Inhibition of papilloma volume was maximal in the 2-himachalen-7-ol IP 25, IP 50 and gavage (48 – 52%; p < 0.01) followed by IP 10 and topical 2.5% (43%: p < 0.05) then cisplatinum (28%; NS) groups. The least gain in body weight was observed with the cisplatinum group. Liver enzymes (ALP, ALT and AST) were not affected in all treated groups; however creatinine and urea levels were significantly higher (p < 0.05) in the cisplatinum group compared to control. In conclusion, 2-himachalen-7-ol has potent antitumor activity against DMBA/TPA skin carcinogenesis with relatively lower toxicity than commonly used chemotherapeutic drugs.